2015
DOI: 10.1016/j.molimm.2014.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced recognition of plasma proteins in a non-native state by complement C3b. A possible clearance mechanism for damaged proteins in blood

Abstract: Complement C3 is a key fluid-phase protein of the immune system that covalently tags pathogenic cells and molecules for subsequent clearance. Previously, we reported that complement activation results in the formation of multiple C3b:plasma protein complexes in serum. However, it is not known if C3b attaches to any plasma protein in close proximity or preferentially binds damaged proteins. The objective of this study was to determine if C3b couples to plasma proteins in a non-native state and if this could be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…However, this conformational change is not negligible and it could partially affect some functionality of BSA. 65,66 Finally, given that BSA did not interact with the adenosine moiety, it is confirmed that it rather interacts with the squalene moiety of the SQAd bioconjugate. This cannot be directly tested since the squalene molecule is insoluble in water, but is not surprising since BSA is known to possess several sites to bind with fatty acids and steroids.…”
Section: Circular Dichroismmentioning
confidence: 77%
See 1 more Smart Citation
“…However, this conformational change is not negligible and it could partially affect some functionality of BSA. 65,66 Finally, given that BSA did not interact with the adenosine moiety, it is confirmed that it rather interacts with the squalene moiety of the SQAd bioconjugate. This cannot be directly tested since the squalene molecule is insoluble in water, but is not surprising since BSA is known to possess several sites to bind with fatty acids and steroids.…”
Section: Circular Dichroismmentioning
confidence: 77%
“…Given the order of magnitude of the binding constant estimated through quenching fluorescence experiment, isothermal titration calorimetry and molecular docking simulations, this should be easily achievable. Finally, the strong reorganization of BSA conformation observed by circular dichroism raises the question of whether all the properties of BSA are retained 65,66.…”
mentioning
confidence: 99%
“…During erythrocyte traffic through sinusoids in liver and spleen, residual phagocytes remove bound immune complexes, leading to their clearance. [11][12][13] Several recent studies using transcriptomics techniques to identify complement proteins in kidney biopsies have provided documentation of an increase of messenger RNA of complement proteins in patients with SLE. During inflammation, there is an increase of such proteins, as well as a decrease of messanger RNA of complement regulators such as CR-1.…”
Section: Complement System Abnormalitiesmentioning
confidence: 99%